Composition, Antioxidant and Anti-inflammatory activities of Hexane and Methanol extracts of Acmella uliginosa from Terai region of Uttarakhand - Kanchan Gairola; Shriya Gururani; Ravendra Kumar; Om Prakash; Sanjeev Agrawal; Shiv Kumar Dubey (Universidade de São Paulo, 2022)
Abstract Acmella uliginosa, an edible herb belonging to Asteraceae family, was collected from the Terai region of Uttarakhand, India. Methanol and hexane extracts of the whole plant were prepared using soxhlet apparatus. The GC-MS analysis of plant extracts identifies 22 and 35 major compounds of methanol and hexane extracts which comprises of 74.21% and 73.20% of the total composition of extracts, respectively. The major compound in hexane was 2, 4-heptadienal (7.99%) whereas trans, trans-9, 12-octadecadienoic acid propyl ester (16.96%) was major compound in methanol extract. The extracts were evaluated for antioxidant and anti-inflammatory properties. Methanol extract showed higher free radical scavenging and reducing power activities with IC50 value 153.82±1.69 μg/mL and RP50 value of 152.28±0.41 μg/mL, respectively. The metal chelating activity was higher in hexane extract as compared to methanol extract i.e., 62.08±0.25 μg/mL. The anti-inflammatory activity assessed by its ability to inhibit denaturation was higher in methanol having IB50 value 87.33±0.15 µg/mL. The total phenolic content (TPC), total flavonoid content (TFC) and ortho-dihydric phenol content (ODP) of methanol and hexane extracts were also evaluated. TPC, TFC and ODP was higher in methanol extract having value of 122.23±0.22, 35.01±0.29 and 8±0.86 mg/mL, respectively. Acmella uliginosa, might be considered as a natural source for antioxidant and anti-inflammatory properties.